Ethical Internet Use Among Teenagers in The Digital Era - Fadil, Cholid; Zuhri, Saifuddin; Alawi, A. Muammar (MultiTech Publisher, 2024)
In today's digital age the use of the Internet in particular social media has become a passion for teenagers. It has led to a decline in ethics and morals in mainstream youth, where social values are becoming one of the identities of indonesians. The article was created because of the writer's interest in bullying and even the death threats made by Indonesian netizens on Thai social media (facebook), which in turn sparked a fight that even prompted hate speech among citizens. The case of course affects Indonesian identity in the eyes of other countries. The main purpose of the article is to learn the level of media awareness and ethics in young children and to analyze how social media ethics can affect national identity. The authors further study using qualitative methods using social social samples (15-17 year old) and supported by the review literature. According to research, the authors have tried to provide some of the problem solutions: socialized media education, maximize family roles as the first